Subtle shifts in fecal microbiota diversity during early stages of Mycobacterium avium subsp. paratuberculosis pathogenesis in dairy cattle - P. Steuer; C. Tejeda; J.M. Hernández-Agudelo; F. Ulloa; M.F. Addis; M. Salgado (Veterinary Microbiology, 2026)

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

DISTRIBUTION OF SPAWNING AND NURSERY GROUNDS FOR DEEP–WATER RED SHRIMPS IN THE CENTRAL WESTERN MEDITERRANEAN SEA - F. PALMAS; P. ADDIS; S. CABIDDU; D. CUCCU; M. C. FOLLESA; M. MURA; A. OLITA; P. PESCI; A. SABATINI (Mediterranean Marine Science, 2014)
The presence of spawning and nursery grounds of Aristeids in the central western Mediterranean Sea were investigated using fishery-independent data (trawl surveys, 1994–2012). Spatial distributions were generated for mature animals and recruits, for both spring/summer and autumn data, using an inverse distance weighted deterministic interpolation. The persistence index was used to identify stable spawning and nursery grounds in the Sardinian slope region for Aristaeomorpha foliacea and Aristeus antennatus. Areas of aggregation for recruits and mature females appear connected with important physical habitat features. The analysis also suggests a seasonal bathymetric distribution for nursery areas. The recruits of A. foliacea are located in the upper part of the continental slope (377-450 m) in spring-summer and reach greater depths (468-628 m) in autumn. For A. antennatus, for which nursery areas only emerge in autumn, there is presumably an opposite ontogenic migration, from deep sea to upper slope, during the summer (575-681 m). Results indicate also a partial overlap between the nursery and spawning grounds of both species. In this particular areas, local environmental conditions such as upwelling events or the presence of canyons and seamounts seem to play an important role in their distribution. This study generated also relevant information on the spatial and temporal distribution of seasonal or persistent aggregations of spawners and recruits, providing scientific elements to suggest the feasibility of protecting these important resources.

Mitochondrial DNA variability of the pipefish Syngnathus abaster - D. Sanna; F. Biagi; H. B. Alaya; F. Maltagliati; A. Addis; A. Romero; J. De Juan; J.‐P. Quignard; A. Castelli; P. Franzoi; P. Torricelli; M. Casu; et al. (Journal of Fish Biology, 2013)
This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish‐water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference ( BI ), maximum likelihood ( ML ) and network analyses, which were consistent in showing three well‐separated clusters of S. abaster populations. Furthermore, BI and ML did not support the monophyly of the taxon S. abaster . These results suggest the occurrence of a species complex in the study area, whose differentiation may have occurred since the Pleistocene. The results also show a very high genetic variability at the inter‐population level, with no shared haplotypes among sites. Evolutionary forces due to the fragmented nature of the brackish‐water habitats may account for the high genetic divergence found among the groups and populations. Finally, although dispersal by rafting over long distances may occasionally occur, this study suggests linear stepping‐stone model of colonization to be most likely. The complexity of the results obtained suggests that further studies are needed to elucidate the phylogeny of S. abaster .

Phylogenetic relationships of freshwater sponges (Porifera, Spongillina) inferred from analyses of 18S rDNA, COI mtDNA, and ITS2 rDNA sequences - John S. Addis; Kevin J. eterson P (Zoologica Scripta, 2005)
The phylogenetic relationships of nine species of freshwater sponges, representing the families Spongillidae, Lubomirskiidae, and Metaniidae, were inferred from analyses of 18S rDNA, cytochrome oxidase subunit I (COI) mtDNA, and internal transcribed spacer 2 (ITS2) rDNA sequences. These species form a strongly supported monophyletic group within the Demospongiae, with the lithistid Vetulina stalactites as the sister taxon. Within the freshwater sponge clade, the basal taxon is not resolved. Depending upon the method of analysis and sequence, the metaniid species, Corvomeyenia sp., or the spongillid species, Trochospongilla pennsylvanica , emerges as the basal species. Among the remaining freshwater sponge species, the spongillids, Spongilla lacustris and Eunapius fragilis , form a sister group to a clade comprised of the spongillid species, Clypeatula cooperensis , Ephydatia fluviatilis , and Ephydatia muelleri , and the lubomirskiid species, Baikalospongia bacillifera and Lubomisrkia baicalensis . C. cooperensis is the sister taxon of E. fluvialitis , and E. muelleri is the sister taxon of ( B. bacillifera + L. baicalensis ). The family Spongillidae and the genus Ephydatia are thus paraphyletic with respect to the lubomirskiid species; Ephydatia is also paraphyletic to C. cooperensis . We suggest that C. cooperensis be transferred to the genus Ephydatia and that the family Lubomirskiidae be subsumed into the Spongillidae.

Analyses of Nuclear ldhA Gene and mtDNA Control Region Sequences of Atlantic Northern Bluefin Tuna Populations - B. Ely; D.S. Stoner; Alvarado J.R. Bremer; J.M. Dean; P. Addis; A. Cau; E.J. Thelen; W.J. Jones; D.E. Black; L. Smith; K. Scott; I. Naseri; et al. (Marine Biotechnology, 2002)